Tanzania : Managing Forest Resources - Mohan, P.C. (World Bank, Washington, DC, 2012)
During the 1970s and 1980s in Tanzania, there was a widespread perception, though a somewhat narrow, and inaccurate one, that high and accelerating rates of deforestation in some areas, was primarily being driven by demand for woodfuel, and construction timber. In order to take a more comprehensive, and strategic view of the sector, the government launched the Tanzania Forestry Action Plan, which covered the period 1990/91-2007/08. The Bank-assisted Tanzania Forest Resources Management Project (FRMP - 1992/99) was formulated to implement the Action Plan, and to generally improve forest management in Tanzania. The note looks at the FRMP - aimed at strengthening the institutions responsible for developing forest, and land policies, as well as regional, and district forestry services in selected areas - through its impact on the ground, and provides a number of lessons learned.